Effects of Atractylodes Macrocephala Rhizoma polysaccharide on intestinal microbiota composition in rats with mammary gland hyperplasia - Ping, Yang; Li, Changxu; Wang, Lihong; Zhao, Hong (Frontiers in Endocrinology, 2023)
Background: In recent years, Mammary gland hyperplasia (MGH) has been considered to be one of the diseases caused by endocrine disorders. It has been shown that diseases caused by endocrine disorders can be treated by regulating intestinal microbial. As a commonly used medicine in clinical practice, Atractylodes Macrocephala Rhizoma has good functions in regulating intestinal homeostasis. Therefore, this paper studied the effect of Atractylodes Macrocephala Rhizoma polysaccharide (AMP), on the intestinal flora of MGH rats, providing a new idea for polysaccharide treatment of MGH. Materials and methods: Twenty-four female SD rats were selected and randomly divided into three groups, blank control group (Con), model control group (Mod) and AMP group, eight rats in each group. MGH rat models were established by estradiol-progesterone combination and treated with AMP gastric infusion. The levels of E2, P and PRL in the serum of rats were measured, the intestinal contents were collected, and 16s rRNA high- throughput sequencing technology was analyzed the changes of intestinal flora in the MGH rats. Results: AMP has good therapeutic effects on MGH rats, decreasing estradiol (E2) and prolactin (PRL) levels and increasing progesterone (P) levels, at the same time, it can regulate the abundance and diversity of intestinal flora of MGH rats, improve the disorder of intestinal flora caused by MGH and change the community structure, increase the abundance of beneficial flora and decrease the abundance of pathogenic flora. Conclusion: AMP can improve the intestinal microbiological environment of MGH rats, maintain the microecological balance of intestinal microbial, and improve MGH symptoms.